Models of talent identification in swimming. - Dimitric, G.; Obradovic, B. (1st International scientific conference: Exercise and quality of life, Novi Sad. March 26/28th 2009, 2009)
There are many conditions necessary for success in modern sport. One of these is an inherent talent or aptitude. Early identification of talent is one of the most important concerns in contemporary sport (Bompa, 1985; Bompa, 1990; Harre, 1982). The basic premise underlying talent is that the development of the youthful athlete can be best served if the athlete trains in a sport of discipline for which he/she is best suited (Harre, 1982). Talent identification is long term process. This process consist of few stages. This work will present some models of talent identification in swimming.